Pengembangan dan Evaluasi Formulasi Sabun Padat Transparan yang Mengandung Ekstrak Kulit Bawang Merah (Allium cepa L.) sebagai Antioksidan - Sukmawati, Sukmawati; Wiryani, Ani Siti; Alsadat, Shena (Jurusan Farmasi, Politeknik Kesehatan Kementerian Kesehatan Aceh, 2025)
Indonesia ranks 17th globally in air pollution levels, with 91% of the population living in areas that exceed WHO safety limits. Air pollution poses various health risks, including skin cancer. Red onion peel, commonly regarded as vegetable waste, contains flavonoids, saponins, and tannins, which possess antioxidant properties. This study investigates the potential of red onion peel extract in soap formulations for skin protection against free radicals. Soaps were formulated with red onion peel extract at concentrations of 4%, 8%, and 12%, and evaluated based on organoleptic characteristics, pH, foam height and stability, and hardness. The results showed that transparent solid soaps containing 4%, 8%, and 12% red onion peel extract were successfully formulated and remained stable across all tested parameters. These findings suggest that red onion peel extract can be effectively incorporated into soap formulations to protect the skin from free radicals. Thus, transparent solid soap containing red onion peel extract represents a promising skincare product, offering antioxidant protection and contributing to skin health and beauty